2023
DOI: 10.26811/peuradeun.v11i1.794
|View full text |Cite
|
Sign up to set email alerts
|

The Capability of Humanskill of the Madrassa Principal Leadership in Managing Human Resources in MAN 2 West Aceh

Abstract: The management of education units needs the human skills of madrasah principal leadership in organizing, mobilizing, and motivating human resources (HR). The purpose of this study was to assess madrasah leadership's human capability in managing human resources at a senior high school in West Aceh. This study used a qualitative method with an interactive naturalistic approach in analyzing the human skill capability of the madrasah principal in managing human resources. Data collection methods were through obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that a person with good job abilities will perform well; the more talents a person have, the more productive the performance will be. (Herman et al, 2023:325) [3] reveals that there is an urgent demand for the capacity of human talents in human resources management. The science and art of managing the roles and relationships of the workforce to enable them to perform productively and successfully toward the objectives of companies is known as human resources management.…”
Section: Trust In Co-workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that a person with good job abilities will perform well; the more talents a person have, the more productive the performance will be. (Herman et al, 2023:325) [3] reveals that there is an urgent demand for the capacity of human talents in human resources management. The science and art of managing the roles and relationships of the workforce to enable them to perform productively and successfully toward the objectives of companies is known as human resources management.…”
Section: Trust In Co-workersmentioning
confidence: 99%
“…The results of Table No. (3) showed that the coefficient of determination (R2) reached (0.755). This means that the dimensions of organizational trust explain an amount of (0.755) of the variance occurring in the development of human resources capabilities, and the rest is due to factors that the study did not examine.…”
Section: Testing Sub-hypothesesmentioning
confidence: 99%
“…Someone with good social skills can readily be accepted by others, build cooperation, form a solid team, and have high empathy (Kurniawan & Idris, 2023). They can maintain friendships with peers and solve problems effectively and academically.…”
Section: A Introductionmentioning
confidence: 99%